The Play “Three Fateful Hills” was staged in the Form of Peking Opera under the Title “Three Mountains” (Mongolian Journal of Arts and Culture, 2025)
D.Natsagdorj’s play “Three fateful hills” (Uchirtai Gurvan Tolgoi) is a classic work that has been staged repeatedly in the theaters of Mongolian. it has also drawn the attention of international theater communities and been performed abroad. For instance, in China the play was adapted into the Beijing opera form as “Three Mountains”, integrating it into the unique cultural traditions of the country and turning it into a part of cultural heritage. “Three fateful hills” exerted a certain influence on the character-creating techniques and conventional roles of Beijing opera, while also introducing innovative changes to stage design. As such, it became a work of great cultural and artistic significance, embodying the explorations and debates over the reform of Beijing opera and the development of traditional national arts, and enriching these processes with progressive ideas.“Учиртай гурван толгой” жүжиг “Гурван уул” нэрээр Бээжин ший жүжгийн хэлбэрээр тоглогдсон ньХураангуй: Д.Нацагдоржийн “Учиртай гурван толгой” жүжиг нь Монгол Улсын театрт олонтоо тавигдсан сонгодог бүтээл юм. Монгол үндэсний өвөрмөц шинжийг агуулсан тус жүжиг нь урилгаар олон улсад тавигдаж байсан баялаг судлагдахуунтай тухайлбал, Хятад улсад бээжин ший хэлбэрээр “Гурван уул” нэрээр тоглогдсон явдал нь Монголын театрын онцлох судалгаа болж байна. “Учиртай гурван толгой” жүжиг нь бээжин шийгийн дүр бүтээх онцлог болон уламжлалт дүрүүдийн арга ажиллагаанд тодорхой хэмжээнд нөлөөлж, тайзны зохион байгуулалтад шинэлэг өөрчлөлт оруулсан юм. “Гурван уул” жүжгийн тоглолт нь тухайн цаг үед үүсээд байсан бээжин шийгийн шинэчлэл ба үндэснийуламжлалт урлагийг хөгжүүлэх чиглэлийн эрэл хайгуулд шинэ туршилт болж үлдсэн ба хоёр орны театрын харилцааны хөгжилд ач холбогдол үзүүлсэн юм.Түлхүүр үгс: Бээжин ший, уламжлалт дүрүүдийн төрөл, уламжлалт тайз засал, Гурван уул